L23 Utilisation of Cognitive AIDS and Quality of Life in HD Patients. (17th September 2014) - Howe, E; van Walsem, MR; Frich, J; Andelic, N
Abstract : Introduction: Patients with Huntington's disease (HD) develop cognitive impairment. While cognitive dysfunction has been found to negatively affect health-related quality of life, studies have shown that cognitive aids can help to improve and maintain quality of life in other patient populations suffering cognitive dysfunction. Objectives: To identify utilisation of cognitive aids in HD patients, and to assess whether there is a correlation between cognitive aids and quality of life. Methods: Through the Oslo University Hospital and Vikersund Rehabilitation Centre all patients with a clinical diagnosis of HD living in the South-East region of Norway have been invited to participate in the study. Currently 80 patients are included and 39 are being followed up. The UHDRS Total Functional Capacity and functional ability scales, and selected items of the Needs and Provision Complexity Scale, which determines met and unmet healthcare needs in patients with complex neurological disabilities, and EQ-5D, a patient self-report measurement for quality of life, are used. Demographic and patient characteristics, information about the use of cognitive aids are recorded. The clinical evaluation of the patients' cognitive status, based on information from the patient and/or next of kin and healthcare professionals is made by the same trained raters. Results: We are currently analysing the collected data, and results will be presented at the conference. Conclusion: Results will give knowledge about the utilisation of cognitive aids in patients with HD, identify unmet needs for such aids, and study any correlations with quality of life. The results may inform stakeholders and clinicians when planning long-term management of HD patients.